Implementasi Manajemen Pendidikan Islam di Madrasah Ibtidaiyah (MI) Al-Islam Umbulharjo Yogyakarta - Sri Erdawati; Arivaie Rahman; Iwan Siswanto (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2020)
This article is a study on the Implementation of Islamic Education Management in Madrasah Ibtidaiyah (MI) Al-Islam Umbulharjo Yogyakarta. The purpose and urgency of this research is to find out and describe how Islamic Education Management is implemented in Madrasah Ibtidaiyah (MI) Al-Islam Umbulharjo Yogyakarta. To achieve that goal, qualitative research is defined as a type of research. As for exploring objects and research data comprehensively, systematically, and validly used descriptive- analysis methods. After being described and analyzed, the results of this study showed that Madrasah Ibtidaiyah (MI) Al-Islam Umbulharjo Yogyakarta already has and implemented eight important Managerial substances that must be present in an Islamic educational institution. The eight Management are: (1). Curriculum Management, (2). Personnel Management, (3). Classroom Management, (4). Student Management, (5). Facility and Infrastructure Management, (6). Financial Management, (7). Community Participation Management, and (8). Principal Leadership Management. Although the eight substances of management have been fulfilled, but in its implementation there is still a small part that is not as expected. For example, in Curriculum Management and Personnel Management, MI Al-Islam Umbulharjo still uses KTSP curriculum and there are still some teachers who are graduates of Senior High School (SMA).